Managing sport for health: An introduction to the special issue. Issue 1 (February 2019) - Edwards, Michael B.; Rowe, Katie
Highlights: Sport should be aligned with community needs and should be empowering. Sport should be adaptable and evolving to ensure sport culture values health. Sport organisations should leverage partnership for health to promote organisational sustainability. Achieving health outcomes requires reshaping sport systems and strategies toward intentional health objectives. Abstract: Sport is often viewed as vehicle to achieve positive health outcomes. While sport's potential to contribute to health is rarely disputed, sport is not always managed in ways that specifically prioritise health objectives, and evidence regarding sport's contribution to health has been inconsistent to date. This special issue was designed to advance a research agenda in relation to the management of sport for health. Articles published in the special issue examine sport management practices that impact health, both positively and negatively. The authors identified three overarching themes, with respect to how sport can be managed towards the achievement of health outcomes: sport should be aligned with community needs and should be empowering; sport should be adaptable and evolving to ensure sport culture values health; and, sport organisations should leverage partnership for health to promote organisational sustainability. In future research, scholars are encouraged to further examine the three identified themes and expand on other findings presented in the special issue, towards a stronger evidence base in relation to the management of sport for health. Opportunities exist to continue to advance knowledge regarding the potential for management strategies, models, and practices to lead to positive-and importantly, negatives-health outcomes through sport. If sport management scholars and practitioners are to meaningfully contribute to health agendas, health objectives must play a central role in reshaping sport systems and strategies toward the achievement of such outcomes.